Report on public participation in industrial and commercial activities (Ministry of Finance [Port of Spain]TT, 1995)
Examines the rationale for governments involvement in industrial and commercial activities. Provides statistical data on the State Enterprise Sector over the period 1982 to 1993. Articulates current government policy on rationalisation of the State Enterprise Sector. Describes the procedures established for the efficent execution of the associated rationalisation programme. Provides an evaluation of the rationalisation process to date.
DC